Persepsi dan Kepuasan Konsumen terhadap Ikan Bandeng Tanpa Duri di Lamongan Berdasarkan Pendekatan IPA–CSI - M Khairul Anam; Bhiaztika Ristyanadi; Masrul Ubaidillah (Universitas Mataram, 2026)
Processed fishery products, such as boneless milkfish, are increasingly in demand among consumers due to their convenience and nutritional value. This study aims to analyze consumer perceptions of boneless milkfish products in Lamongan Regency and to measure the level of customer satisfaction using the Importance–Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The research employed a quantitative approach, utilizing an online questionnaire distributed to 115 respondents who had previously consumed boneless milkfish products. The results of the IPA indicate that attributes such as taste, price, packaging, presentation, stock availability, as well as safety and consumer trust, fall into Quadrant I (high importance–low performance), signifying that these aspects require immediate improvement. Attributes including texture and overall product quality are categorized in Quadrant II (high importance–high performance), indicating that their performance should be maintained. Meanwhile, accessibility and ease of transaction are placed in Quadrant III (low importance–low performance), suggesting lower priority for improvement, whereas product size is categorized in Quadrant IV (low importance–high performance), indicating potential overinvestment. Furthermore, the Customer Satisfaction Index (CSI) value was calculated at 79.76%, demonstrating that consumers are generally satisfied with boneless milkfish products. In conclusion, several key attributes require strategic improvements by business actors in order to enhance overall consumer satisfaction and competitiveness in the market.